Whole genome re-sequencing reveals artificial and natural selection for milk traits in East Friesian sheep - Li, Xiaolong; Yuan, Lvfeng; Wang, Weimin; Zhang, Deyin; Zhao, Yuan; Chen, Jiangbo; Xu, Dan; Zhao, Liming; Li, Fadi; Zhang, Xiaoxue (Frontiers in Veterinary Science, 2022)
The East Friesian sheep is one of the important high-yielding dairy sheep breeds, but still little is known about their genetic and genomic variation during domestication. Therefore, we analyzed the genomic data of 46 sheep with the aim of identifying candidate genes that are closely related to milk production traits. Our genomic data consisted of 20 East Friesian sheep and 26 Asian Mouflon wild sheep. Finally, a total of 32590241 SNPs were identified, of which 0.61% (198277) SNPs were located in exonic regions. After further screening, 122 shared genomic regions in the top 1% of FST and top 1% of Nucleotide diversity ratio were obtained. After genome annotation, these 122 candidate genomic regions were found to contain a total of 184 candidate genes. Finally, the results of KEGG enrichment analysis showed four significantly enriched pathways (P<0.05): beta-Alanine metabolism (SMOX, HIBCH), Pathways in cancer (GLI2, AR, TXNRD3, TRAF3, FGF16), Non-homologous end-joining (MRE11), Epstein-Barr virus infection (TRAF3, PSMD13, SIN3A). Finally, we identified four important KEGG enrichment pathways and 10 candidate genes that are closely related to milk production in East Friesian sheep. These results provide valuable candidate genes for the study of milk production traits in East Friesian sheep and lay an important foundation for the study of milk production traits.